2010
DOI: 10.2174/1874357901004010109
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Type 1/Adeno-Associated Virus Hybrid Vectors

Abstract: Herpes simplex virus type 1 (HSV-1) amplicons can accommodate foreign DNA of any size up to 150 kbp and, therefore, allow extensive combinations of genetic elements. Genomic sequences as well as cDNA, large transcriptional regulatory sequences for cell type-specific expression, multiple transgenes, and genetic elements from other viruses to create hybrid vectors may be inserted in a modular fashion. Hybrid amplicons use genetic elements from HSV-1 that allow replication and packaging of the vector DNA into HSV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 242 publications
0
3
0
Order By: Relevance
“…This study also raises possibilities of designing both viral and non-viral vectors with LEDGF/p75 fusion proteins targeting safer genomic sites. Hybrid HSV/AAV vectors have been constructed in an attempt to combine the large insert cloning capacity of non-integrating HSV vectors (up to 150 kb) with the site-specific integration property of AAV vectors into a genomic hotspot, the AAVS1 locus, and to a certain extent, randomly (De Oliveira & Fraefel, 2010). Other HSV-based hybrid vectors include the episomally maintained HSV/EBV and randomly integrating HSV/RV vectors.…”
Section: Novel and Hybrid Viral Vectorsmentioning
confidence: 99%
“…This study also raises possibilities of designing both viral and non-viral vectors with LEDGF/p75 fusion proteins targeting safer genomic sites. Hybrid HSV/AAV vectors have been constructed in an attempt to combine the large insert cloning capacity of non-integrating HSV vectors (up to 150 kb) with the site-specific integration property of AAV vectors into a genomic hotspot, the AAVS1 locus, and to a certain extent, randomly (De Oliveira & Fraefel, 2010). Other HSV-based hybrid vectors include the episomally maintained HSV/EBV and randomly integrating HSV/RV vectors.…”
Section: Novel and Hybrid Viral Vectorsmentioning
confidence: 99%
“…This study also raises possibilities of designing both viral and non-viral vectors with LEDGF/p75 fusion proteins targeting safer genomic sites. Hybrid HSV/AAV vectors have been constructed in an attempt to combine the large insert cloning capacity of non-integrating HSV vectors (up to 150 kb) with the site-specific integration property of AAV vectors into a genomic hotspot, the AAVS1 locus, and to a certain extent, randomly (De Oliveira & Fraefel, 2010). Other HSV-based hybrid vectors include the episomally maintained HSV/EBV and randomly integrating HSV/RV vectors.…”
Section: Novel and Hybrid Viral Vectorsmentioning
confidence: 99%
“…For example, plasmid-based HSV pseudoviral amplicon vectors show great promise in gene therapy and have been studied for several decades [25,26]. Studies have shown that long-term transgene expression can be achieved when the AAV rep gene is added along with the transgene of interest into the HSV-1 amplicon plasmid, with the transgene flanked with AAV inverted terminal repeat elements (ITRs) [27][28][29].…”
Section: Introductionmentioning
confidence: 99%